von Willebrand Factor Activity Detected in a Monoclonal Antibody-based ELISA: an Alternative to the Ristocetin Cofactor Platelet Agglutination Assay for Diagnostic Use - Murdock, Paul J; Woodhams, Barry J; Matthews, Kathy B; Pasi, K John; Goodall, Alison H (Thrombosis and Haemostasis, 1997)
The monoclonal antibody RFF-VIII:R/1 recognises an epitope on von Willebrand factor involved in its interaction with GPIbα. A two-site, solid phase ELISA has been established using RFF-VIII:R/1 as the solid-phase, capture antibody and an enzyme-conjugated, polyclonal antibody to human VWF, which provides an assay for VWF functional activity with a detection limit of 0.5 U/dl VWF and an interassay %CV<10. Plasma from 192 VWD patients (48 studied retrospectively; 144 prospectively) showed VWF levels of <50 U/dl in type 1 patients (n = 156), <25 U/dl in type 2A (n = 26) and <35 U/dl in type 2B (n = 8) which, in type 1 and 2A patients, correlated with RiCoF activity (r >0.82). In plasma from patients with type 1 VWD values of VWF in the Mab-based ELISA were similar to levels of VWF:Ag measured in a polyclonal antibody-based ELISA (r >0.87) but were significantly lower than VWF:Ag in type 2A and 2B plasmas (p <0.0005), allowing discrimination of variant VWD. The Mab-based ELISA has advantages of sensitivity and reproducibility over the RiCoF assay to measure VWF activity and can be used to analyse stored samples. In conjunction with an ELISA for VWF:Ag and VWF multimer analysis, it provides a reliable method, for the laboratory diagnosis of VWD.